ENGLISH NOUNS OFTEN CONFUSED IN ROMANIAN - Andreea Moise (Studii de gramatică contrastivă, 2016)
The current paper presents several English nouns that are often confused in Romanian on the grounds of either their similar pronunciation in the English language, or similar translation of the respective nouns into the Romanian language. The present paper exemplifies by showing the usage of the respective nouns in different contexts and by explaining the reasons for the correct usage of the nouns. Beside the explanation in English of the meaning of nouns in different contexts, each noun is provided with a translation into the Romanian language in order for the nouns to be accurately comprehended by the Romanian speakers. Therefore, the paper intends to render a useful guidance in what regards an adequate usage of the easily mistaken English nouns, starting from easily confused nouns to more complex ones.